DEMO reactor design using the new modular system code SYCOMORE. (15th June 2015) - Reux, C.; Di Gallo, L.; Imbeaux, F.; Artaud, J.-F.; Bernardi, P.; Bucalossi, J.; Ciraolo, G.; Duchateau, J.-L.; Fausser, C.; Galassi, D.; Hertout, P.; Jaboulay, J.-C.; et al.
Abstract: A demonstration power plant (DEMO) will be the next step for fusion energy following ITER. Some of the key design questions can be addressed by simulations using system codes. System codes aim to model the whole plant with all its subsystems and identify the impact of their interactions on the design choices. The SYCOMORE code is a modular system code developed to address key questions relevant to tokamak fusion reactor design. SYCOMORE is being developed within the European Integrated Tokamak Modelling framework and provides a global view (technology and physics) of the plant. It includes modules to address plasma physics, divertor physics, breeding blankets, shield design, magnet design and the power balance of plant. The code is coupled to an optimization framework which allows one to specify figures of merit and constraints to obtain optimized designs. Examples of pulsed and steady-state DEMO designs obtained using SYCOMORE are presented. Sensitivity to design assumptions is also studied, showing that the operational domain around working points can be narrow for some cases.